Propranolol: A Promising Therapeutic Avenue for Classic Kaposi Sarcoma - Genedy, Rasha Mahmoud; Owais, Marwa; El Sayed, Naglaa Mohamed (Dermatology Practical & Conceptual, 2025)
Introduction: Kaposi sarcoma (KS) is a low grade angio-proliferative tumor of endothelial origin. Human herpes virus 8 (HHV8) plays a major role in the pathogenesis of KS. Classic Kaposi sarcoma is commonly seen among elderly of Mediterranean origin. It is usually slowly progressive and is rarely fatal. There is no definitive cure for KS. Beta blockers were used with great success in the treatment of infantile hemangioma. Because of some similarity between infantile hemangioma and Kaposi sarcoma, topical beta blockers were tried with variable success rate.Objectives: We aimed to assess the efficacy and safety of oral propranolol in the treatment of classic Kaposi sarcoma.Methods: Fifteen patients diagnosed with classic Kaposi sarcoma were prospectively enrolled in the study. Detailed history and full clinical examination were conducted. Histopathological diagnosis with confirmatory immune staining was done for all patients. Oral propranolol in a dose of 60 mg was given per day for 6 months. The patients assessed clinically as complete responders, partial responders, and non-responders.Results: Nine patients (60%) were partial responders; showed 50% reduction in the number of the existing lesions, and 6 patients (40%) were considered non-responders; 3 with stable disease and 3 with progressive disease. Lymphedema partially improved in 1 patient.Conclusions: Oral propranolol is a safe and good option for treatment of patients with non-complicated classic Kaposi sarcoma, especially elderly with multiple comorbidities.